The heterogeneous labor market impacts of the Covid-19 pandemic - Guido Matias; Eliza C. Forsythe (W.E. Upjohn Institute for Employment Research, 2020)
We study the distributional consequences of the Covid-19 pandemic's impacts on employment. Using CPS data on stocks and flows, we show that the pandemic has exacerbated pre-existing inequalities. Although employment losses have been widespread, they have been substantially larger in lower-paying occupations and industries. Individuals from disadvantaged groups, such as Hispanics, younger workers, those with lower levels of education, and women, have suffered both larger increases in job losses and larger decreases in hiring rates. Occupational and industry affiliation can explain only part of the increased job losses among these groups.
Keywords: E24; J21; J31; J62; J63; 330; Covid-19; CPS; job losses; occupations; industries; distributional impacts